2010
DOI: 10.1002/adfm.200902210
|View full text |Cite
|
Sign up to set email alerts
|

Original Fuel‐Cell Membranes from Crosslinked Terpolymers via a “Sol–gel” Strategy

Abstract: Hybrid organic/inorganic membranes that include a functionalized (‐SO3H), interconnected silica network, a non‐porogenic organic matrix, and a ‐SO3H‐functionalized terpolymer are synthesized through a sol–gel‐based strategy. The use of a novel crosslinkable poly(vinylidene fluoride‐ter‐perfluoro(4‐methyl‐3,6‐dioxaoct‐7‐ene sulfonyl fluoride)‐ter‐vinyltriethoxysilane) (poly(VDF‐ter‐PFSVE‐ter‐VTEOS)) terpolymer allows a multiple tuning of the different interfaces to produce original hybrid membranes with improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…The low dependence of temperature to proton conductivity may be related to a continuous network of ionic domains, thus facilitating proton migration [52]. This was confirmed by SAXS measurements which showed that lamellar structure resulted from both M50 and M60 membranes [49] at 100% RH.…”
Section: Proton Conductivitymentioning
confidence: 65%
See 1 more Smart Citation
“…The low dependence of temperature to proton conductivity may be related to a continuous network of ionic domains, thus facilitating proton migration [52]. This was confirmed by SAXS measurements which showed that lamellar structure resulted from both M50 and M60 membranes [49] at 100% RH.…”
Section: Proton Conductivitymentioning
confidence: 65%
“…The general feature is a gradual decay of intensity scaling as q -2 over more than one decade of angles which may be assigned to a lamellar morphology [46][47][48][49]. Two very broad scattering maxima modulate this intensity decay and can be observed at about 0.1 and 0.01 Å -1 .…”
Section: Membrane Morphologiesmentioning
confidence: 99%
“…PEMFCs operating above 100 C are preferred over that operating at low temperature to overcome several disadvantages (like CO catalyst poisoning and heat and water management) associated with the later [1,6,7,24]. Inferior proton conductivity of Nafion at high temperature and low humidity has prompted towards the development of new polymer membranes such as polyethersulfone (PES) [25,26], polyetheretherketone (PEEK) [27][28][29][30], polyimide (PI) [31][32][33], polybenzimidazole (PBI) [34][35][36][37][38][39][40][41], polystyrene-acrylonitrile (SAN) [42,43], and polyvinylidene fluoride (PVDF) [44][45][46] to meet the U. S. Department of Energy (DOE) targets [47,48].…”
Section: Development Of Polymer Membranes For Fuel Cell Applicationsmentioning
confidence: 99%
“…[4,5] Hybrid organic-inorganic materials may meet all these requirements. [6][7][8] Recently, we reported the development of such hybrid systems, where a rigid highly ordered silica colloidal crystal containing a continuous network of nanopores provides mechanical and thermal stability, non-swelling and water retaining properties, while polymer brushes grown on the surface of silica and having sulfonic groups provide proton conductivity. [9] Highly-ordered silica colloidal crystals could serve as good inorganic matrix materials for DMFC proton conductive membranes, however they are limited by size, since it is challenging to obtain uniform and evenly thick free-standing membrane of large size (e.g.…”
Section: Introductionmentioning
confidence: 99%